Sixty-month follow up of three different universal adhesives used with a highly-filled flowable resin composite in the restoration of non-carious cervical lesion - Oz, Fatma Dilsad; Ozturk, Canan; Soleimani, Reza; Gurgan, Sevil (Springer Berlin Heidelberg, 2022)
OBJECTIVE: The purpose of this clinical trial was to evaluate and compare the performances of three different universal adhesives used with a highly filled flowable universal resin composite in the restoration of non-carious cervical lesions (NCCLs) over a 60-month period. MATERIAL AND METHODS: Ninety-nine NCCLs were restored at 18 participants. NCCLs were divided into three different universal adhesive groups: Clearfil Universal Bond (CU) (n = 31), iBOND Universal (IU) (n = 33), and G-Premio Bond (GP) (n = 35). Prior to the adhesive procedures, selective enamel etching was performed with 37% phosphoric acid in all experimental groups. Adhesive systems were applied following the manufacturers’ instructions, and the lesions were restored with a highly filled flowable resin composite (G-ænial Universal Flo). Restorations were finished and polished immediately after placement. All restorations were scored with regard to retention, marginal discoloration, marginal adaptation, sensitivity, surface texture, and color match using modified United States Public Health Service (USPHS) criteria after 1 week (baseline) and 6, 12, 18, 24, 36, and 60 months. Statistical analyses were performed using chi-square and McNemar’s and Kaplan Meier tests. The level of significance was set at p < 0.05. RESULTS: After 60 months, the recall rate was 72.2%. Survival rates of CU, IU, and GP restorations were 87%, 85.2%, and 96.5%, respectively. Five CU (25%), 8 IU (34.8%), and 12 GP (42.9%) restorations exhibit bravo scores for marginal adaptation. However, no differences were seen among them. CU showed lower bravo score than IU and GP for marginal discoloration (CU, 0%; IU, 26.1%; GP, 32.1%). Two CU, 7 IU, and 6 GP restorations showed bravo scores for surface texture, and 2 (9.1%) CU and 1 (3.3%) GP restorations were scored as bravo score for color match (p > 0.05). CONCLUSION: The tested universal adhesives showed similar success rates during the 60-month follow-up. However, CU showed better clinical performance than IU and GP in terms of marginal adaptation and discoloration. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT03415412 CLINICAL RELEVANCE: The long-term clinical performances of the three universal adhesives in the restoration of NCCLs using selective enamel etching mode were successful after 60 months.